Analisis Pendekatan Mimetik dalam Menggali Makna Puisi “Merayakan Kehilangan” Karya Ulfiyanti Nawangsih Rahayu - Desta Aldi Pratama; Dian Ayu Puspita Sari; Eka Wening Safitri; Faiza Najma Khoirunissa; Maulida Alfi Sa’adah (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
A literary work is a work that not only has beauty, but also has meaning in it. Poetry is an imaginative work with words that contain aesthetics and simplicity, but is difficult to understand for readers who have little knowledge in analyzing poetry. Someone who likes to write uses poetry as motivation. The author is interested in analyzing the poem "Celebrating Loss" by Ulfiyanti Nawangsih Rahyu because it has deep meaning. This research aims to understand the meaning of Ulfiyanti Nawangsih Rahayu's poetry and increase the author's experience in the mimetic approach. The method used in this research uses a qualitative descriptive method which produces descriptive data in the form of words and then explains the meaning of the poem "Celebrating Loss" using mimetic studies.